Identifying Factors for the Effectiveness of the Design Mindset within the Creative Industry - Villamar, Pamela V. (2014)
The design mindset, characteristic of the Creative Industry, is being highly valued by organisations interested in creative models that can potentially boost innovation. However, how this mindset works beyond the implementation phase of these models have received scant attention. The goal of the research is to identify the factors in the effectiveness of the design mindset within the Creative Industry. For this purpose, a literature review that links this mindset with the organisational design used by this sector is conducted. In addition, an empirical approach performing a data collection consisting in an in-depth interview and surveys is presented and analysed. Accordingly, the findings of the research will show a set of enablers and barriers that might affect the performance of this mindset. These set of factors prove to be strongly related to key concepts like openness, flexibility and complexity, in relation to the structure, operations, management and creative workforce of an organisation, within the sector of study. The findings of this research aim to provide a set of guidelines to organisations that want to adopt creative models, preparing them better to implement and maintain these models over time.